Application of covered stent graft in the treatment of complex carotid artery lesions: A single center experience. (December 2022) - Liu, Changya; Shen, Yin; Qian, Kang; Hu, Yueyun; Hu, Xuebin; Wu, Xinxin
Purpose: To assess the clinical efficiency and imaging outcome of applying covered stent grafts for the treatment of complex carotid artery lesions. Method: A total of 39 consecutive patients with carotid artery lesions treated with covered stent grafts at our institution from December 2016 to December 2019 were reviewed. Two kinds of stent including self-expandable covered stent (Viabahn; W. L. Gore & Associates) and balloon-expandable covered stent (Willis; Microport) were applied. The angiograms immediately after the procedure, perioperative complications, and follow-up outcomes were recorded. Result: Based on imaging features, 11 patients exhibited pseudoaneurysms, 23 patients had blood blister-like aneurysms (BBAs), and five patients were carotid cavernous fistulas. A total of 40 stent implantations were performed, including nine Viabahn stents and 31 Willis stents. Two patients received double implants of Willis stents. Stent failed to perform for one patient due to tortuous parent artery. The angiography reports immediately after the procedure showed that the lesions in 36 patients were completely occluded, whereas two patients had minimal endoleaks. With respect to the occurrence of procedural complications, an aneurysm ruptured during the procedure in one case, which resulted in CCF, and acute in-stent thrombosis occurred in another case. Clinical and angiographic follow-up (11.2±2.4 months) sessions were conducted for 38 patients and a complete lesion exclusion was achieved in 36 patients. The minimal endoleak persisted in one patient and another patient experienced recurrence with stent migration, leading to ipsilateral blepharoptosis. However, none of the patients developed hemorrhage or ischemia and in-stent stenosis was not observed. Conclusion: Covered stent grafts appear to be a safe and feasible for the treatment of complex carotid artery lesions. Despite the potential for stent delivery failure as well as endoleak and procedure-related complications, covered stent grafts should be considered when selecting the optimal treatment strategy.